Efeitos do tratamento crônico com extrato de cannabis rico em canabidiol na modulação cardiovascular de ratos com hipertensão renovascular - Souza, Rayane Maria Pessoa de (2022)
Cannabis sativa (CS) is a genus of plants that has been widely used since antiquity, currently its medicinal use is released in Brazil, from which phytocannabinoids are derived, such as cannabidiol (CBD), which has neuroprotective, anti-inflammatory and antioxidant effects. Some studies suggest that CS-derived CBD may influence the cardiovascular system. In this work, the effects of a Cannabis Extract rich in cannabidiol (Ecbd) were verified in cardiovascular modulation of rats with model 2K1C hypertension. For this, in vivo protocols were used with Wistar rats submitted to surgical 2K1C or SHAM who after four weeks received Ecbd was administered by gavage (twice a day for two weeks), from the following groups: SHAM, SHAM+Ecbd, 2K1C e 2K1C+Ecbd. Thus, after six weeks of surgery, the effect of chronic treatment with Ecbd on mean arterial pressure (MAP, mmHg), heart rate (HR, bpm), chemoreflex, baroreflex sensitivity and autonomic activity was evaluated. The results showed that the treatment with Ecbd promoted a reduction in the MAP of the rats 2K1C+Ecbd (2K1C+Ecbd: 138,7 ± 9,6 vs. 2K1C: 170,8 ± 7,5 mmHg) but did not change the HR of the animals. Ecbd treatment improved baroreflex sensitivity (2K1C+Ecbd: -2,1 ± 0,1 vs. 2K1C: -1,8 ± 0,06 bpm.mmHg-1), as well as reduced the hypotensive response induced by the ganglionic block in the animals 2K1C+Ecbd (2K1C+Ecbd: ∆-50,0 ± 3,4 vs. 2K1C: ∆-92,5 ± 13,4 mmHg), however, there was no change in cardiovascular responses to peripheral chemoreflex activation. Our studies suggest the hypotensive potential of Ecbd treatment in rats with renovascular hypertension model 2K1C.